Synthesis of lignosulfonate-assisted flower-like titanate nanostructures and their excellent performance for heavy metal removal. Issue 7 (15th May 2016) - Chang, Yongfang; Han, Wei; Cai, Aijun; Wang, Huiying
Abstract: Lignosulfonate-assisted titanate nanoflowers (L-TNFs) were synthesized by a simple solvothermal method. The structure, morphology and adsorption capacity of the product were investigated. The characterization results confirm that L-TNFs are amorphous materials with mesoporous structure. In comparison with common TNFs, L-TNFs enhance their adsorption capacity for heavy metal ions. The adsorption isotherms are well fitted to a Langmuir adsorption model, and the maximal adsorption capacities of Pb(II), Cu(II) and Cd(II) on L-TNFs are 586.2, 166.5 and 175.9 mg g −1, respectively. The results suggest that L-TNFs are a promising adsorbent for the removal of heavy metals from aqueous solution.